Quantificação da biomassa foliar de Nectandra megapotamica (Spreng.) Mez - Rocha Júnior, Dilson Sousa (2013)
This study aimed to quantify and describe the leaf biomass for trees Nectandra megapotamica (Spreng.) Mez in the region of Cologne Fourth of Italian Immigration, RS. Data collection was conducted in the locality of Val Feltrina, in the city of Silveira Martins and Novo São Paulo, in the city of Agudo, both located in the central region of Rio Grande do Sul. We sampled 36 trees, and 20 belonged to sociological position under canopy and 16 belonged to the canopy. These trees were sampled branches and these compounds extracted branches simple. In subjects canopy, sampling branches compounds occurred randomly among the apical branches. In the under canopy trees, branches compounds were removed in three bands position in the canopy. The following dendrometric variables were obtained for each sample: diameter at breast height, total height, base diameter, cross-sectional area at breast height, cross-sectional area of the base, full length, length rolling, green leaf biomass and dry leaf biomass. Only under canopy trees, the following morphometric variables were measured: insertion height of the crown, mean radius of the crown, crown projection area, crown length, formal of the crown, ratio h/d, degree of the crown, coverage index and salience index. Among the dendrometric variables, length rolling presented the highest correlation with leaf biomass, both branches simple and compound under canopy and canopy as for the trees under canopy. For the same length rolling, there was a greater production of green leaf biomass and dry leaf biomass the samples from the canopy. The position of the branches compounds in the treetops did not significantly influence the production of green leaf biomass and dry leaf biomass. Among the morphometric variables, the crown area, then the diameter of the crown, had the highest correlation with green leaf biomass and dry leaf biomass. The formal of the crown, degree of the crown and coverage index were not correlated with the trees leaf biomass of canela-preta under canopy. The ratio of green leaf biomass and dry leaf biomass with the length rolling does not differ between the trees of canela-preta and branches compounds under canopy.